An alternatively spliced heat shock transcription factor, OsHSFA2dI, functions in the heat stress‐induced unfolded protein response in rice. (7th January 2015) - Cheng, Q.; Zhou, Y.; Liu, Z.; Zhang, L.; Song, G.; Guo, Z.; Wang, W.; Qu, X.; Zhu, Y.; Yang, D.; Flemetakis, E.
Abstract As sessile organisms, plants have evolved a wide range of defence pathways to cope with environmental stress such as heat shock. However, the molecular mechanism of these defence pathways remains unclear in rice. In this study, we found that OsHSFA2d, a heat shock transcriptional factor, encodes two main splice variant proteins, OsHSFA2dI and OsHSFA2dII in rice. Under normal conditions, OsHSFA2dII is the dominant but transcriptionally inactive spliced form. However, when the plant suffers heat stress, OsHSFA2d is alternatively spliced into a transcriptionally active form, OsHSFA2dI, which participates in the heat stress response (HSR). Further study found that this alternative splicing was induced by heat shock rather than photoperiod. We found that OsHSFA2dI is localised to the nucleus, whereas OsHSFA2dII is localised to the nucleus and cytoplasm. Moreover, expression of the unfolded protein response (UNFOLDED PROTEIN RESPONSE) sensors, OsIRE1, OsbZIP39/OsbZIP60 and the UNFOLDED PROTEIN RESPONSE marker OsBiP1, was up‐regulated. Interestingly, OsbZIP50 was also alternatively spliced under heat stress, indicating that UNFOLDED PROTEIN RESPONSE signalling pathways were activated by heat stress to re‐establish cellular protein homeostasis. We further demonstrated that OsHSFA2dI participated in the unfolded protein response by regulating expression of OsBiP1.